2021
DOI: 10.3389/fmicb.2021.663414
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of mcr-1.1-Producing Escherichia coli Recovered From Human Infections in São Paulo, Brazil

Abstract: Polymyxins are one of most important antibiotics available for multidrug-resistant Gram-negative infections. Diverse chromosomal resistance mechanisms have been described, but the polymyxin resistance phenotype is not yet completely understood. The objective of this study was to characterize colistin resistant mcr-1-producing strains isolated from human infections over one year in a hospital setting (Hospital das Clínicas, São Paulo, Brazil). We isolated 490 colistin-resistant Gram-negative rods, of which eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…It is the diverse genetic mechanisms of the mcr-1-carrying IncI and IncHI2/HI2A plasmids that cause the high horizontal transfer rate of mcr-1, e.g., the mcr-1-related insertion element ISApl1 (1,070 bp; Zhong et al, 2018), which was originally discovered in Actinobacillus pleuropneumoniae (Tegetmeyer et al, 2008), is the most important mobile element of the IS30 family mediating the spread of mcr-1. The Tn6330 transposon (ISApl1-pap2-mcr-1-ISApl1) can mediate the horizontal transfer of mcr-1, in which ISApl1 forms a ringshaped intermediate in a "cut-and-paste" manner to mediate the spread of mcr-1 among different types of plasmids (Girardello et al, 2021). In the QH20-5D4-1 isolate, the transposon element ISApl1 was present downstream of mcr-1, and the pap2 gene present upstream of mcr-1 encodes the phospholipase closely related to the horizontal transmission of mcr-1 (Ma et al, 2021), both playing a very important role in mcr-1 mediated bacterial colistin resistance (Choi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It is the diverse genetic mechanisms of the mcr-1-carrying IncI and IncHI2/HI2A plasmids that cause the high horizontal transfer rate of mcr-1, e.g., the mcr-1-related insertion element ISApl1 (1,070 bp; Zhong et al, 2018), which was originally discovered in Actinobacillus pleuropneumoniae (Tegetmeyer et al, 2008), is the most important mobile element of the IS30 family mediating the spread of mcr-1. The Tn6330 transposon (ISApl1-pap2-mcr-1-ISApl1) can mediate the horizontal transfer of mcr-1, in which ISApl1 forms a ringshaped intermediate in a "cut-and-paste" manner to mediate the spread of mcr-1 among different types of plasmids (Girardello et al, 2021). In the QH20-5D4-1 isolate, the transposon element ISApl1 was present downstream of mcr-1, and the pap2 gene present upstream of mcr-1 encodes the phospholipase closely related to the horizontal transmission of mcr-1 (Ma et al, 2021), both playing a very important role in mcr-1 mediated bacterial colistin resistance (Choi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mcr-1.1 was reported in E. coli isolate obtained from wound drainage ( Eltai et al 2020 ) from Qatar. Girardello et al (2021) reported the presence of mcr-1.1 in E. coli clinical isolate in Sao Paulo, and mcr-1.1 was found in two K. pneumoniae clinical isolates by Rocha et al (2020) .…”
Section: Discussionmentioning
confidence: 98%
“…The genomic context analysis of the genome location of mcr-1.1 revealed that of the mcr-1.1 - pap2 cassette was present in this work. A variety of mcr-1.1 - pap2 cassette compositions have been shown, suggesting the ability of mcr-1 to mobilize across the genes ( Girardello et al, 2021 ; Snesrud et al, 2016 ). IS Apl1 flanking the mcr-1.1 - pap2 cassette conferred the transposition and was found to be lost after mobilization ( Snesrud et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%